KINERJA DINAS PERINDUSTRIAN DAN TENAGA KERJA DALAM MENINGKATKAN KUALITAS TENAGA KERJA DI KABUPATEN MAGELANG - Hanna Saputri; Rian Destiningsih (JURNAL EKOMBIS, 2020)
Human Resources has a very important and strategic role in achieving various development goals. Various training and education are carried out as an effort to improve the skills and quality of the workforce. The main problem of employment in Magelang Regency in 2018 is the low quality of the workforce, which is characterized by the low level of formal education undertaken. This study aims to see and describe the performance of the Department of Industry and Labor in Magelang Regency in improving the quality of labor in Magelang Regency. This research uses a qualitative method with a descriptive approach. The data in this study were obtained by using questionnaire, observation, and secondary data techniques. The data was obtained from employees of the Magelang Regency Disperinnaker and the people who received services from the Magelang Regency Disindinnaker and Manpower Office. This research shows that the performance of the Department of Industry and Labor (Disperinnaker) of Magelang Regency in an effort to improve the quality of labor in Magelang Regency is quite good, seen from the training and education held in an effort to improve the skills of the workforce. Another aspect is to look at the services provided such as providing information, readiness in providing services and placement of workers that have been carried out effectively and efficiently.  Keywords: performance, labor, quality